2021
DOI: 10.1088/1361-648x/abf7a0
|View full text |Cite
|
Sign up to set email alerts
|

Quasiparticle electronic structure of two-dimensional heterotriangulene-based covalent organic frameworks adsorbed on Au(111)

Abstract: The modular nature and unique electronic properties of two-dimensional (2D) covalent organic frameworks (COFs) make them an attractive option for applications in catalysis, optoelectronics, and spintronics. The fabrications of such devices often involve interfaces formed between COFs and substrates. In this work, we employ the first-principles GW approach to accurately determine the quasiparticle electronic structure of three 2D carbonyl bridged heterotriangulene-based COFs featuring honeycomb–kagome lattice, … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 92 publications
0
2
0
Order By: Relevance
“…For each interface structure, we consider the optical absorption of light polarized along either the armchair or the zigzag direction of BP, which gives rise to the optical anisotropy of pristine monolayer BP. The GW -BSE approach systematically improves over local and semilocal density functional calculations of quasiparticle and optical properties of heterogeneous interfaces, thanks to its capturing of the long-range dielectric screening, crucial in an accurate description of the interfacial level alignment. , In addition to standard GW -BSE calculations, we further develop a new computational analysis tool to decompose the excited states of the interface (as calculated from BSE) into different contributions, useful in understanding the nature of each peak in the absorption spectra and unraveling the interface effect in modulating the excitonic properties of each individual component.…”
Section: Introductionmentioning
confidence: 99%
“…For each interface structure, we consider the optical absorption of light polarized along either the armchair or the zigzag direction of BP, which gives rise to the optical anisotropy of pristine monolayer BP. The GW -BSE approach systematically improves over local and semilocal density functional calculations of quasiparticle and optical properties of heterogeneous interfaces, thanks to its capturing of the long-range dielectric screening, crucial in an accurate description of the interfacial level alignment. , In addition to standard GW -BSE calculations, we further develop a new computational analysis tool to decompose the excited states of the interface (as calculated from BSE) into different contributions, useful in understanding the nature of each peak in the absorption spectra and unraveling the interface effect in modulating the excitonic properties of each individual component.…”
Section: Introductionmentioning
confidence: 99%
“…χ mol 0 can be calculated efficiently in a smaller simulation cell than the interface (thanks to the local nature of the molecule) followed by a real-space mapping procedure . χ sub 0 can be calculated efficiently in a unit cell of the substrate (thanks to its periodicity) followed by a reciprocal-space folding procedure. , It has been widely shown that these acceleration techniques and eq work very well for molecules physisorbed on substrates and van der Waals heterostructures. We note that the discussions above specifically apply to GW calculations using a plane-wave basis, and similar subsystem-based partitioning schemes for the polarizability have been developed for GW calculations using localized basis and in the context of time-dependent DFT. , …”
mentioning
confidence: 99%